Integration of systems engineering and project management using a management flight simulator - Jonkers, Raymond Klaas, author; Shahroudi, Kamran Eftekhari, advisor; Young, Peter, advisor; Bradley, Thomas, committee member; Valdes-Vasquez, Rodolfo, committee member (Colorado State University. Libraries, 2020)
Cost overruns and schedule delays are pervasive in complex projects despite the use of systems engineering and traditional project management models and tools. These disciplines can often work in isolation leading to inconsistencies in product information, tracking of design changes and challenges in decision-making. While literature proposes philosophical approaches to integrating these disciplines, there does not appear to be a practical approach offered. The current study proposes a practical approach by way of a management flight simulator that integrates systems engineering and management models for data-driven risk-informed decision-making. This simulator provides immediate feedback on whether a change is going to help or disrupt design integrity through the monitoring of system attribute trends and cues. It also provides the impact on lifecycle management curves using a system dynamics sub-model. From this feedback, several system, policy and process levers are available within the simulator for what-if scenarios with the goal to improve product, organizational and project performance. The value in the emergent properties of the simulator as a decision support system is viewed as greater than from the sum of its sub-models. In developing the simulator, integration requirements, systems thinking, systems science and systems engineering practices are leveraged to develop an integration strategy. For bringing multiple disciplines together to address design changes risks, a response strategy is proposed that includes aspects of set-based goal-based design and agile management practices.
Keywords: integration; project management; systems engineering; models; digital thread; simulator